Trophic ecology of the puma (Puma concolor) within an agricultural ecosystem - Gheler-Costa, Carla; Botero, Gabriel Pavan; Reia, Lais [UNESP]; De Cassia Gilli, Leticia; Comin, Fabio Henrique; Verdade, Luciano Martins (My University, 2018)
Carnivores are important ecological components of ecosystems since they control abundance, distribution and diversity of prey populations. They are keyspecies in the maintenance and restoration of diversity and resilience of ecosystems. The Puma concolor (onça-parda) is a forest mammal with wide distribution in the western hemisphere. Its requirements in area size, life span and feed are a restriction factor on the survival of the species due to hunting pressure, prey decrease and deforestation. Current analysis evaluates the diet of P. concolor in a silvicultural environment in the state of São Paulo, Brazil. The environment comprises savannah remnants, plantations of eucalyptus trees and pasture. One hundred and three excrement samples were retrieved, selected and analyzed. Results show the consumption of great amounts of fowl and small-size mammals. Feed differs from that of species within their natural habitat where preyed mammals are the main items. Diet variation confirms the puma as a generalist predator consuming available preys without any preference for certain species.
Ecologia trófica de onça-parda (Puma concolor) em paisagem agrícola
Keywords: Agro-ecosystem; Carnivores; Conservation; Diet